2018
DOI: 10.1093/sleep/zsy158
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean diet pattern and sleep duration and insomnia symptoms in the Multi-Ethnic Study of Atherosclerosis

Abstract: Sleep duration and sleep quality are important predictors of risk for cardiovascular disease (CVD). One potential link between sleep health and CVD is through lifestyle factors such as diet. To clarify the association between diet and sleep, we assessed the associations of sleep duration and insomnia symptoms with current Mediterranean-style diet (aMed) and with historical changes in aMed score. Actigraphy-measured sleep duration and self-reported insomnia symptoms categorized as insomnia with short sleep (<6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 55 publications
2
80
2
1
Order By: Relevance
“…Findings of the current investigation provide an important extension to that study by corroborating this relation in US individuals, whose habitual dietary patterns are distinct from Europeans, as reflected by different measures of the Mediterranean diet tailored for use in the respective populations (MEDAS vs. aMed). Our findings are also consistent with those of the only other study conducted in a US population, which showed that greater compliance with an aMed diet predicted lower risk for insomnia in the Multi-Ethnic Study of Atherosclerosis [21]. The current study, however, provides unique insight beyond that of any previous investigation by identifying specific components of sleep quality to which this Mediterranean diet-sleep relation extends, including higher sleep efficiency and fewer sleep disturbances.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Findings of the current investigation provide an important extension to that study by corroborating this relation in US individuals, whose habitual dietary patterns are distinct from Europeans, as reflected by different measures of the Mediterranean diet tailored for use in the respective populations (MEDAS vs. aMed). Our findings are also consistent with those of the only other study conducted in a US population, which showed that greater compliance with an aMed diet predicted lower risk for insomnia in the Multi-Ethnic Study of Atherosclerosis [21]. The current study, however, provides unique insight beyond that of any previous investigation by identifying specific components of sleep quality to which this Mediterranean diet-sleep relation extends, including higher sleep efficiency and fewer sleep disturbances.…”
Section: Discussionsupporting
confidence: 89%
“…It is unclear if these findings would extend to US populations, given differential patterns of health behaviors and exposure to distinct psychosocial, environmental, and structural influences on health across cultures. To our knowledge, only one analysis, within the Multi-Ethnic Study of Atherosclerosis, evaluated the aMed diet in relation to sleep in US adults [21]. Although results showed that this diet pattern predicted lower odds of insomnia and short sleep, associations with measures of general sleep quality were not evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to depression, recent studies suggested a relationship between sleep duration and Mediterranean Diet. In the MESA Sleep ancillary study, a higher adherence to a Mediterranean-type diet was associated with a 43% greater likelihood of achieving 6–7 h of sleep per night compared to 6 h [ 81 ]. Data from the Seniors-ENRICA and Hellenic Longitudinal studies also found a lower likelihood of poor sleep quality for those who were following a Mediterranean diet [ 82 , 83 ].…”
Section: Methodsmentioning
confidence: 99%
“…Dietary patterns can refer to those defined a priori through a validated score or defined a posteriori through data-driven methods. Higher adherence to a Mediterranean diet pattern, a validated score, associated with fewer insomnia symptoms in a diverse US population [ 17 ] and healthier dietary patterns (identified through data-driven methods) associated with better sleep quality over time in peri-menopausal Mexican women [ 18 ].…”
Section: Introductionmentioning
confidence: 99%